(untitled) (Global Journal of Human-Social Science, 2013)
The purpose of this study is to test the reliability and validity of Metacognition Scale MS developed by Demir 2012 with a view to identifying perceptions of Education Faculty students regarding metacognitive activities The participants of the study are 250 randomly chosen students who attend three different departments in Kafkas University Education Faculty The data were analysed through exploratory and confirmatory factor analysis to enhance the construct validity Internal consistency Cronbach Alpha co-efficiency was evaluated for the reliability of the instrument A 14-item instrument with evaluation organization and planning sub-dimensions was developed as a result of the analyses conducted Cronbach Alpha internal consistency co-efficiency that explains 53 074 of the total variance was found 87 for the first factor 65 for the second factor 70 for the third factor and 89 in total